The Effectiveness of The Problem-Based Learning Model in Improving Conceptual Understanding in Physics Education: A Systematic Literature Review - Shelliana Iqlima; Windy Zaerani; Gunawan Gunawan (Indonesian Journal of Applied Science and Technology, 2023)
Conceptual understanding is an essential competency in physics education that supports students' ability to solve contextual problems. Problem-Based Learning (PBL) is considered an effective approach for enhancing conceptual understanding through authentic problem-solving activities. This study aims to analyze the effectiveness of PBL in improving senior high school students' conceptual understanding of physics, identify factors influencing its effectiveness, and map research trends from 2014 to 2023. A Systematic Literature Review (SLR) using the PRISMA approach was conducted. A total of 52 articles retrieved from Google Scholar, ERIC, SINTA, and Scopus were screened based on predefined inclusion criteria, resulting in 15 eligible studies. The findings indicate that most studies reported positive effects of PBL on students' conceptual understanding of physics. The integration of technologies, such as PhET simulations, augmented reality, and virtual experiments, also supported the effectiveness of PBL. The most frequently reported influencing factors were problem quality, the teacher's role as a facilitator, and students' readiness. These findings suggest that PBL is a promising instructional approach for improving conceptual understanding in senior high school physics.